Expression of a drought-responsive helix-loop-helix transcription factor OsbHLH061 in rice (Oryza sativa ssp. japonica) - Pham, Thi Minh Thu; Kim, Yeon-Ki; Nahm, Baek-Hie (Academia Journal of Biology, 2025)
Water scarcity poses a significant global challenge for agriculture, growing increasingly severe and widespread. Urgent measures are needed to develop crops that can withstand drought conditions. Recently, the method of transferring genes, particularly transcription factors, has emerged as a promising approach to enhance plant tolerance to stress. Genes are selected based on their differential expression patterns during stress, which can be identified through transcriptome analysis. In this research, the helix-loop-helix transcription factor OsbHLH061 was identified among up-regulated genes in microarray data derived from mRNA extracted from rice plants exposed to various abiotic stresses. The increased expression of OsbHLH061 under drought conditions was confirmed by quantitative real-time PCR (qRT-PCR). Its promoter analysis using the GUS reporter gene revealed spatial regulation of OsbHLH061 in germinating seeds, leaves, and root tips of young seedlings. Overexpression of OsbHLH061 was achieved by introducing the gene into rice plants under the control of the promoter of Rab21 in response to abscisic acid 21. However, transgenic plants did not exhibit any significant advantages in drought resistance compared to wild-type plants. These findings suggested the need for a different expression system. Moreover, the lack of significant changes in phenotype despite altering this transcription factor indicated a multi-locus nature of drought resistance associated with this gene.